A Primer on Human Capital - Flabbi, Luca; Gatti, Roberta (World Bank, Washington, DC, 2018)
This note summarizes some of the key contributions in the macro- and micro- economic literature on the pathways linking human capital and income growth. Rather than completeness, the objective of this work is to distill some of the most relevant threads in the evolution of these literatures using a human capital lens, with a view to provide a useful yet parsimonious conceptual framework and an update on empirical results. The note first describes the human capital model (section 1). It then outlines the main theoretical elements of growth theory and presents empirical results from the cross-country regressions and development accounting literature to gauge to what extent human capital affects growth at the aggregate level (sections 2, 3 and 4). The note then reviews the micro empirical literature estimating labor income returns of human capital investments (sections 5 and 6). The conclusion draws comparisons between the two empirical approaches and provides a brief critical assessment on how to interpret the empirical results. Investing in human capital is a promising strategy to attain stable and positive growth. The magnitude of the effects is country-specific and varies depending on the population of interest, the policy under consideration, and the human capital component considered.